Bilateral patellar cyst: A case report with an Ironman triathlete - Knechtle, B.; Wengler, E.; Nikolaidis, P. T. (The Journal of Sports Medicine and Physical Fitness, 2018)
Cysts can occur in many shapes and forms in the human body. A cyst is defined as a closed cavity, or sac, that is lined with epithelium. Any cyst can contain liquid or semisolid material, can be normal or abnormal, and can occur in soft tissue or in bone. Considering cysts in bones and especially in the knee, patellar cysts are very rare and most of the patellar cysts are described as primary or secondary aneurysmal bone cysts.1 In the literature, patellar cysts are mainly reported as case reports2`3 where generally one knee is affected.